Fourth European Conference on Universal Multiservice Networks (ECUMN'07) 2007
DOI: 10.1109/ecumn.2007.7
|View full text |Cite
|
Sign up to set email alerts
|

Approach for Reducing Control Packets in AODV-Based MANETs

Abstract: Movements of nodes in MANETs result in route changes, thus requiring the transmission of control packets. As MANETs have limited resources, it is important to reduce the number of control packets which consume bandwidth. We propose a AODV-based protocol which uses a backbone network to reduce control packets. The destination location is given by GPS and transmitted to the source by the backbone network. Our routing algorithm limits the route search to zones smaller than those used by the original AODV (Ad hoc … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Mobile ad hoc network is increasingly promising area of research but they increase the cost of the network in many cases. Lot of research work has been reported on AODV protocol for the reduction in routing overhead [3,4,18,25]. Many of them concentrate on the routing efficiency rather than route discovery.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Mobile ad hoc network is increasingly promising area of research but they increase the cost of the network in many cases. Lot of research work has been reported on AODV protocol for the reduction in routing overhead [3,4,18,25]. Many of them concentrate on the routing efficiency rather than route discovery.…”
Section: Related Workmentioning
confidence: 99%
“…This on demand characteristics is the major advantage of AODV. Improvements of AODV have been a major attraction in the research work [12,18 ]. The main purpose of the present study is to exploit the route establishment in AODV.…”
Section: Introductionmentioning
confidence: 99%